Development and validation of a new questionnaire for the assessment of patients with diabetic foot disease: The Diabetic Foot Questionnaire (DiaFootQ) - Ruiz-Muñoz, María; Fernández-Torres, Raúl; Formosa, Cynthia; Gatt, Alfred; Pérez Panero, Alberto José; Pérez-Belloso, Ana J.; Martínez-Barrios, Francisco-Javier; González-Sánchez, Manuel (Elsevier, 2024)
Background The epidemiology data and global burden of diabetic foot disease underscores the need for effective prevention strategies, which requires an early diagnosis. Patient-reported outcome measures are instruments based on a simple format, which favours their application. Currently, there is an absence of instruments with a broad enough scope to capture the diverse aspects involved in diabetic foot disease. Objectives To develop a questionnaire for the assessment of patients with diabetic foot disease and carry out an analysis of its validity and reliability. Methods The study was developed in two stages. Stage 1: the Delphi Panel was composed of 22 experts. The questionnaire is made up of 25 questions selected, after three rounds, from an initial sample of 68 questions. Stage 2: A validation study was performed. With a sample of 273 subjects, an exploratory factor analysis and an analysis of internal consistency, items response, and validity were carried out using the Diabetes Quality of Life, SF-12v2, Foot Function Index and EuroQol EQ5D questionnaires. Measurements of error and sensitivity to change were also analyzed. Results A 25-item questionnaire (DiaFootQ) was developed. It comprised two dimensions: 1) lifestyle and function; and 2) footwear and foot self-care. Sample (n=273) mean age was 69.77 years (±11.08). The internal consistency of DiafootQ was α=0.916, and item response values were ICC=0.862–0.998. External validity correlation levels ranged from r=0.386 to r=0.888. Conclusion DiaFootQ was developed. Integrating the main aspects involved in diabetic foot disease could help to detect more accurately the risk or severity of these patients. DiaFootQ is a well-structured, valid, and reliable tool whose use should be promoted in clinical and research settings.
Keywords: Diabetes - Complicaciones y secuelas; Pies - Lesiones y heridas; Diabetes; Evaluation; Questionnaire; Patient-reported outcome; Prevention